Doped sulfide solid electrolyte, method for preparing the same, electrode sheet, and solid-state battery
Patent Information
- Application Number
- CN202610992516.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请提供一种掺杂硫化物固态电解质及其制备方法、极片以及固态电池,旨在改善低温状态下硫化物固态电池性能下降的问题
[0012]本申请实施例采用球磨法来制备掺杂硫化物固态电解质,该方法具有操作简单、能耗低、适配连续规模化生产的突出优势,为硫化物固态电池在低温场景的实用化突破提供了关键技术路径。
Smart Images

Figure CN123018104A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to a sulfide-doped solid electrolyte and its preparation method, electrode sheet, and solid-state battery. Background Technology
[0002] Solid-state batteries use solid electrolytes instead of traditional electrolytes and separators, fundamentally improving battery safety and effectively overcoming the risks of combustion, leakage, and high-temperature decomposition. The stable physicochemical properties of solid electrolytes also broaden the battery's operating temperature range and promise ultra-long cycle life. More importantly, by matching high-energy-density positive and negative electrode materials (such as high-nickel ternary / lithium metal anodes), the energy density of all-solid-state batteries is expected to exceed 500 Wh / kg, meeting future extreme energy demands. Therefore, solid-state batteries have become a global hotspot for research and industrial development.
[0003] Currently, the technological routes for solid-state battery research and development broadly include oxide-based solid-state batteries, sulfide-based solid-state batteries, and halide-based solid-state batteries. Among them, sulfide-based solid-state batteries are currently the focus of research for industrial applications due to their high room-temperature ionic conductivity and excellent processability. However, at low temperatures, sulfide electrolytes such as Li6PS5Cl (LPSC) suffer from several challenges. These include a significant decrease in ionic conductivity due to an increased activation barrier, solid-solid contact failure caused by sluggish reaction kinetics, continuous thickening of the passivation layer due to instability at the positive and negative electrode interfaces, and lithium dendrite growth. These factors make it difficult for sulfide solid-state batteries to achieve stable operation at low temperatures, greatly limiting their commercialization. Summary of the Invention
[0004] This application provides a doped sulfide solid electrolyte, its preparation method, electrode, and solid battery, aiming to improve the performance degradation problem of sulfide solid batteries at low temperatures.
[0005] This application provides a doped sulfide solid electrolyte, wherein the doped sulfide solid electrolyte is a sulfide solid electrolyte co-doped with cations and anions, wherein the cations include Ta 5+ 、Nb 5+ Sb 5+ 、Ge 4+ Mo 4+ Sn 4+ Si 4+ Al 3+ In 3+ Fe 2+ Fe 3+ and Zn 2+ At least one of the following, the anion including F - Cl - ,Br - I - Te2- Se 2- N 3- and BH4 - At least three of them.
[0006] The doped sulfide solid electrolyte provided in this application embodiment, through precise control of cation and anion co-doping strategies, can not only effectively improve the interfacial stability between the positive and negative electrode active materials and the sulfide electrolyte under low-temperature conditions, but also significantly enhance the lithium-ion diffusion capability under low-temperature environments by optimizing the crystal structure. At the same time, the interface optimization brought about by co-doping endows the electrode-electrolyte interface with good mechanical flexibility, which can effectively alleviate the stress damage caused by electrode volume shrinkage at low temperatures and greatly reduce the solid-solid contact loss at the active material / electrolyte interface.
[0007] Optionally, in some embodiments of this application, the chemical formula of the doped sulfide solid electrolyte is: Li 5.5 P 1- x Ta x S 4.5 F a Cl 1.5-a-b-c Br b I c , of which 0 <x≤0.1,0<a≤1,0<b≤1,0<c≤1。
[0008] Optionally, in some embodiments of this application, 0.02≤x≤0.08, 0.1≤a≤0.2, 0.4≤b≤0.6, and 0.1≤c≤0.2.
[0009] When the above-mentioned doped sulfide solid electrolyte is used in a battery, an antioxidant LiTaO3 / LiF gradient positive electrode composite interface layer and a LiBr / LiI / LiF negative electrode dynamic adaptive interface layer can be formed during the early cycle of the battery.
[0010] Accordingly, this application also provides a method for preparing the above-mentioned doped sulfide solid electrolyte, including: Premixes are provided, which include raw materials for sulfide solid electrolytes and dopant sources; Premixed materials are processed into doped sulfide solid electrolytes by ball milling, high-temperature quenching, or liquid phase methods.
[0011] Optionally, in some embodiments of this application, the chemical formula of the doped sulfide solid electrolyte is: Li 5.5 P 1- x Ta x S 4.5 F a Cl 1.5-a-b-c Br b Ic , of which 0 <x≤0.1,0<a≤1,0<b≤1,0<c≤1; Methods for preparing doped sulfide solid electrolytes include: Li2S, P2S5, LiCl, LiBr, LiI, TaCl5 and TaF5 were mixed according to the molar ratio of (2+2.5x) : (1-x) / 2 : (1.5-bc-5x) : b : c : (xa / 5) : a / 5 to obtain a premix. The premix was ball-milled to obtain an amorphous precursor. The amorphous precursor was calcined to obtain a sulfide-doped solid electrolyte.
[0012] This application uses ball milling to prepare doped sulfide solid electrolytes. This method has the outstanding advantages of simple operation, low energy consumption, and adaptability to continuous large-scale production, providing a key technical path for the practical breakthrough of sulfide solid batteries in low-temperature scenarios.
[0013] Optionally, in some embodiments of this application, the ball milling time is 5h to 75h; and / or, the ball milling speed is 200rpm to 1300rpm; and / or, the ball-to-material ratio is (1 to 50):1.
[0014] Optionally, in some embodiments of this application, the calcination temperature of the calcination treatment is 200℃~600℃; and / or, the calcination time of the calcination treatment is 2h~7h; and / or, the calcination treatment is constant temperature calcination.
[0015] Accordingly, this application also provides an electrode, comprising an electrode active material and the doped sulfide solid electrolyte or the doped sulfide solid electrolyte prepared by the above-mentioned method, wherein the electrode active material is mixed with the doped sulfide solid electrolyte.
[0016] Optionally, in some embodiments of this application, the electrode further includes a conductive agent, and the mass ratio of the electrode active material, the doped sulfide solid electrolyte, and the conductive agent is (5~35):(64.5~90):(0.5~5); and / or, the electrode active material is a positive electrode active material, which includes at least one of NCM, LiFePO4, LiCoO2, and LRMOs.
[0017] In addition, this application also provides a solid-state battery, including the aforementioned electrode. Attached Figure Description
[0018] Figure 1This is a conductivity test spectrum of the doped sulfide solid electrolyte provided in Preparation Example 1 of the exemplary embodiments of this application; Figure 2 This is a SEM image of the doped sulfide solid electrolyte provided in Preparation Example 1 of the exemplary embodiments of this application; Figure 3 Figure (a) is a TEM image of the positive electrode of the solid-state battery provided in Embodiment 1 of the exemplary embodiments of this application after 10 cycles; Figure 3 Figure (b) is a TEM image of the positive electrode of the solid-state battery provided in Comparative Example 1, which is an exemplary embodiment of this application, after 10 cycles; Figure 4 Figure (a) is a SEM image of the negative electrode of the solid-state battery provided in Embodiment 1 of the exemplary embodiments of this application after 10 cycles; Figure 4 Figure (b) is a SEM image of the negative electrode of the solid-state battery provided in Comparative Example 1, which is provided in an exemplary embodiment of this application, after 10 cycles. Detailed Implementation
[0019] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0020] This application provides a sulfide-doped solid electrolyte, its preparation method, an electrode, and a solid-state battery. These are described in detail below. It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative and do not impose numerical requirements or establish an order. Various embodiments of the present invention may exist in a range format; it should be understood that the description in a range format is merely for convenience and brevity and should not be construed as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that a range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single digits within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Additionally, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0021] This application provides a solid-state battery, which may include, but is not limited to, at least one of battery cells, battery modules, and battery packs.
[0022] In some embodiments of this application, the solid-state battery is a single battery cell (also called a battery cell). The single battery cell includes an electrode assembly comprising a positive electrode and a negative electrode, which are disposed opposite to each other. The electrode assembly also includes a solid electrolyte membrane disposed between the positive and negative electrode plates to enable ion conduction and prevent short circuits caused by contact between the positive and negative electrode plates. Optionally, the solid electrolyte membrane comprises a sulfide-doped solid electrolyte.
[0023] In some embodiments of this application, the positive electrode sheet includes a positive electrode active material layer. Optionally, the positive electrode sheet also includes a positive electrode current collector, on which the positive electrode active material layer is disposed. As an example, the positive electrode current collector includes aluminum foil. Specifically, the positive electrode active material layer contains a positive electrode active material. As an example, the positive electrode active material includes, but is not limited to, at least one of lithium iron phosphate (LiFePO4), lithium nickel manganese oxide (NCM), lithium cobalt oxide (LiCoO2), and lithium-rich manganese-based layered oxides (LRMOs). Optionally, the positive electrode active material layer also includes at least one of a conductive agent and a binder. As an example, in the positive electrode sheet, the conductive agent includes at least one of carbon black, graphite, carbon nanotubes (CNTs), graphene, and carbon fibers, and the binder includes polyvinylidene fluoride (PVDF). Optionally, the positive electrode active material layer also includes a doped sulfide solid electrolyte.
[0024] In some embodiments of this application, the negative electrode sheet includes a negative electrode active material layer. Optionally, the negative electrode sheet further includes a negative electrode current collector, on which the negative electrode active material layer is disposed. As an example, the negative electrode current collector includes copper foil. Specifically, the negative electrode active material layer contains a negative electrode active material. As an example, the negative electrode active material includes at least one of lithium metal negative electrode, carbon-based negative electrode material, and silicon-based negative electrode material. The lithium metal negative electrode can be elemental lithium or a lithium alloy. Optionally, the negative electrode active material layer also includes at least one of a conductive agent and a binder. As an example, in the negative electrode sheet, the conductive agent includes at least one of carbon black, graphite, carbon nanotubes (CNTs), graphene, and carbon fiber, and the binder includes at least one of styrene-butadiene rubber (SBR) and polyacrylic acid (PAA). Optionally, the negative electrode active material layer also includes a doped sulfide solid electrolyte.
[0025] In some embodiments of this application, during the assembly of the solid-state battery, the assembly pressure is controlled to be ≥75 kPa to ensure close contact between the solid electrolyte membrane and the electrode material, eliminate interfacial voids, and ensure efficient transport of lithium ions at the electrolyte / electrode interface.
[0026] This application also provides an electrode sheet comprising an electrode active material and a doped sulfide solid electrolyte, wherein the electrode active material and the doped sulfide solid electrolyte are mixed. Here, the electrode sheet can be a positive electrode sheet or a negative electrode sheet. When the electrode sheet is a positive electrode sheet, the electrode active material is a positive electrode active material; when the electrode sheet is a negative electrode sheet, the electrode active material is a negative electrode active material. Optionally, the electrode active material is a positive electrode active material, which includes at least one of NCM, LiFePO4, LiCoO2, and LRMOs.
[0027] In some embodiments of this application, the electrode further includes a conductive agent, and the mass ratio of the electrode active material, the doped sulfide solid electrolyte, and the conductive agent is (5~35):(64.5~90):(0.5~5). The electrode active material, the doped sulfide solid electrolyte, and the conductive agent are mixed. As an example, the mass ratio of the electrode active material, the doped sulfide solid electrolyte, and the conductive agent is 35:64.5:0.5, 28:70:2, 17:80:3, or 5:90:5.
[0028] This application also provides a sulfide-doped solid electrolyte, wherein the sulfide-doped solid electrolyte is a sulfide solid electrolyte co-doped with cations and anions, wherein the cations include Ta 5+ 、Nb 5+ Sb 5+ 、Ge 4+ Mo 4+ Sn 4+ Si 4+ Al 3+ In 3+ Fe 2+ Fe 3+ and Zn 2+ At least one of the following, the anion including F - Cl - ,Br - I - Te 2- Se 2- N 3- and BH4 - At least three of them.
[0029] Optionally, sulfide solid electrolytes include LPSC sulfide solid electrolytes (LPSC for short). LPSC is an inorganic lithium-conducting material based on a sulfide-germanium sulfide structure, characterized by high ionic conductivity and soft plasticity. It should be noted that LPSC is not a single compound, but rather refers to a series of lithium-phosphorus-sulfur-chloride compounds with similar structures. For example, LPSC includes Li6PS5Cl and Li... 5.5 PS 4.5 Cl 1.5Li6PS5Cl is a common formulation of lithium-phosphorus-sulfur-chloride compounds, with a sulforaphite-germanium ore structure and high ionic conductivity; Li 5.5 PS 4.5 Cl 1.5 It is a variant of Li6PS5Cl, which modulates lattice parameters and ion migration pathways through chlorine doping.
[0030] Doped sulfide solid electrolytes can be obtained by co-doping cations and anions into sulfide solid electrolytes. Taking LPSC as an example, LPSC is co-doped with cations and anions. The cations partially replace the P sites in LPSC, and the anions partially replace the S sites and / or Cl sites in LPSC, thereby obtaining a doped sulfide solid electrolyte.
[0031] Experiments revealed that single-ion doping modification of LPSC, such as doping with Sn, effectively improved its performance. 4+ Si 4+ 、Ge 4+ O 2- Cl - ,Br - I - Plasma doping alone forms an alloy layer that promotes Li + Uniform deposition and stable lattice enhance high-voltage stability, while increasing lattice site disorder improves ionic conductivity, thereby improving the electrochemical performance of low-temperature sulfide solid-state batteries.
[0032] However, single-ion doping often only improves the performance of one electrode (positive or negative) in a battery, making it difficult to simultaneously meet the comprehensive requirements of good interfacial stability, sufficient mechanical strength, high ionic conductivity, and a wide voltage window. Furthermore, the improvement effect of single-ion doping is relatively limited in addressing the mechanical instability of solid-solid contacts and the slow interfacial ion dynamics at low temperatures.
[0033] The doped sulfide solid electrolyte provided in this application embodiment, through precise control of cation and anion co-doping strategies, can not only effectively improve the interfacial stability between the positive and negative electrode active materials and the sulfide electrolyte under low-temperature conditions, but also significantly enhance the lithium-ion diffusion capability under low-temperature environments by optimizing the crystal structure. At the same time, the interface optimization brought about by co-doping endows the electrode-electrolyte interface with good mechanical flexibility, which can effectively alleviate the stress damage caused by electrode volume shrinkage at low temperatures and greatly reduce the solid-solid contact loss at the active material / electrolyte interface.
[0034] The co-doping modification scheme adopted in this application not only improves the low-temperature service performance of sulfide solid-state batteries, but also further enhances the rate performance and cycle stability of the batteries.
[0035] In some embodiments of this application, the chemical formula of the doped sulfide solid electrolyte is: Li 5.5 P 1- x Ta x S 4.5 F a Cl 1.5-a-b-c Br b I c , of which 0 <x≤0.1,0<a≤1,0<b≤1,0<c≤1。
[0036] The above-mentioned doped sulfide solid electrolyte is based on the sulfide solid electrolyte Li 5.5 PS 4.5 Cl 1.5 CCP-doped Ta 5+ F - ,Br - I - Optionally, 0 < x < 0.1, 0 < a < 1, 0 < b < 1, 0 < c < 1. Further, 0.02 ≤ x ≤ 0.08, 0.1 ≤ a ≤ 0.2, 0.4 ≤ b ≤ 0.6, 0.1 ≤ c ≤ 0.2. As an example, x is 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, or 0.08; a is 0.1, 0.15, or 0.2; b is 0.4, 0.45, 0.5, 0.55, or 0.6; and c is 0.1, 0.15, or 0.2.
[0037] When the above-mentioned doped sulfide solid electrolyte is used in a battery, an antioxidant LiTaO3 / LiF gradient positive electrode composite interface layer and a LiBr / LiI / LiF negative electrode dynamic adaptive interface layer can be formed during the early cycle of the battery.
[0038] The formation principle of the antioxidant LiTaO3 / LiF gradient cathode composite interface layer is as follows: When the battery is first charged to a high voltage, the surface of the cathode material is in a strong oxidizing environment; the metastable Ta in the sulfide-doped solid electrolyte... 5+ and F - They preferentially undergo oxidation and migration over sulfide and phosphorus anion groups. They react with residual lithium compounds (such as Li2O and Li2CO3) or lattice oxygen on the surface of the positive electrode active material particles. On the side closer to the positive electrode, LiTaO3 with good structural stability and lithium-ion conduction is mainly generated. LiTaO3 can effectively inhibit the release of lattice oxygen from the positive electrode and further oxidation and decomposition of the doped sulfide solid electrolyte. On the side closer to the electrolyte, LiF and possibly F-containing complexes are enriched. LiF has an extremely wide electrochemical window and can provide high-voltage protection for the doped sulfide solid electrolyte. Finally, a gradient interface layer is formed from the positive electrode to the electrolyte, with the composition gradually changing from LiTaO3-rich to LiF-rich.
[0039] The formation principle of the LiBr / LiI / LiF anode dynamic adaptive interface layer is as follows: During the first discharge of the battery, the anions in the sulfide-doped solid electrolyte will undergo reduction decomposition in order of reduction potential from high to low. The reduction order is approximately: F - >Br - >I - >S 2- F, which has extremely high electronegativity - Preferential reduction yields nano-LiF, which possesses extremely high chemical stability and mechanical strength, making it an excellent "barrier" component in SEI; LiBr then reacts with LiI to form: Br - and I - The reduction potential of Li is higher than that of the sulfide matrix, therefore it will react with Li before the sulfide is largely reduced. + The combined formation of LiBr and LiI, two lithium salts, exhibits higher ionic conductivity and better interfacial wettability / plasticity than LiF. The resulting SEI is not homogeneous but consists of a dense, stable inner layer of LiF and an outer layer of LiBr / LiI with high ionic conductivity and some deformation capability. During cycling, when the interface undergoes volume changes or localized damage, this plastic-rich, highly ionic-conductive composite layer can adaptively repair itself through localized dissolution-redeposition, maintaining interfacial integrity and smooth ion transport.
[0040] This application also provides a method for preparing the above-mentioned doped sulfide solid electrolyte, including: Premixes are provided, which include raw materials for sulfide solid electrolytes and dopant sources; Premixed materials are processed into doped sulfide solid electrolytes by ball milling, high-temperature quenching, or liquid phase methods.
[0041] The premix is a raw material for synthesizing doped sulfide solid electrolytes. It includes not only the raw materials used to prepare the sulfide solid electrolyte but also the dopant source. As an example, the raw materials for preparing the sulfide solid electrolyte include Li₂S, P₂S₅, and LiCl, and the dopant sources include LiBr, LiI, TaCl₅, and TaF₅.
[0042] Ball milling is a preparation technique based on solid-state reactions. It primarily utilizes mechanical energy (such as impact and shear forces) to mix raw materials at the atomic level and disrupt their crystal lattice, promoting chemical reactions to form sulfide electrolytes. The preparation of doped sulfide solid electrolytes using ball milling mainly involves two stages: ball milling and calcination. Ball milling is conducted at low temperatures (room temperature or cooling). The high-speed collisions between the milling beads not only mix the raw materials but also disrupt their crystalline structure, promoting solid-state reactions. The product obtained after ball milling is an amorphous or partially crystalline powder. This powder is then placed in a sintering furnace under inert gas protection for high-temperature calcination to improve the material's crystallinity, remove residual stress, and form a stable sulfide electrolyte.
[0043] High-temperature melting and quenching is a preparation technique based on liquid-phase reaction. It utilizes the complete melting of raw materials at high temperatures, followed by rapid cooling (quenching) to solidify the material. The preparation of doped sulfide solid electrolytes using this method mainly involves three stages: heating and melting, quenching and cooling, and annealing. Heating completely melts the raw materials, and holding the temperature for a period ensures sufficient reaction and the formation of a homogeneous melt. Rapidly cooling the melt to room temperature prevents crystal growth, preserving the amorphous structure of the material and resulting in a glassy sulfide solid electrolyte with high ionic conductivity. Annealing adjusts the microstructure and ion transport channels of the sulfide solid electrolyte.
[0044] The liquid phase method uses organic solvents as a medium to dissolve or disperse raw materials in the solvent for chemical reactions, and finally obtains the product through drying and heat treatment.
[0045] In some embodiments of this application, the chemical formula of the doped sulfide solid electrolyte is: Li 5.5 P 1- x Ta x S 4.5 F a Cl 1.5-a-b-c Br b I c , of which 0 <x≤0.1,0<a≤1,0<b≤1,0<c≤1; Methods for preparing doped sulfide solid electrolytes include: Li2S, P2S5, LiCl, LiBr, LiI, TaCl5 and TaF5 were mixed according to the molar ratio of (2+2.5x) : (1-x) / 2 : (1.5-bc-5x) : b : c : (xa / 5) : a / 5 to obtain a premix. The premix was ball-milled to obtain an amorphous precursor. The amorphous precursor was calcined to obtain a sulfide-doped solid electrolyte.
[0046] This application uses ball milling to prepare doped sulfide solid electrolytes. This method has the outstanding advantages of simple operation, low energy consumption, and adaptability to continuous large-scale production, providing a key technical path for the practical breakthrough of sulfide solid batteries in low-temperature scenarios.
[0047] In some embodiments of this application, the ball milling time is 5h to 75h. As examples, the ball milling time is 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h, or 75h.
[0048] In some embodiments of this application, the ball milling speed is 200 rpm to 1300 rpm. As examples, the ball milling speed is 200 rpm, 400 rpm, 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, or 1300 rpm.
[0049] In some embodiments of this application, the ball-to-material ratio in the ball milling process is (1~50):1. The ball-to-material ratio refers to the mass ratio between the grinding balls and the premixed material during the grinding process. As examples, the ball-to-material ratio is 1:1, 10:1, 20:1, 30:1, 40:1, or 50:1.
[0050] In some embodiments of this application, the calcination temperature for the calcination treatment is 200°C to 600°C. As examples, the calcination temperature is 200°C, 300°C, 400°C, 500°C, or 600°C.
[0051] In some embodiments of this application, the calcination time is 2h to 7h. As examples, the calcination time is 2h, 3h, 4h, 5h, 6h or 7h.
[0052] In some embodiments of this application, the calcination process is constant-temperature calcination, that is, after the temperature is raised to the target temperature, it is kept at a fixed temperature.
[0053] The following description is based on specific embodiments.
[0054] Preparation Example 1 This preparation example provides a doped sulfide solid electrolyte, and the preparation process of the doped sulfide solid electrolyte is as follows: S1. In an argon glove box, place the raw materials anhydrous Li2S (>99.9%), anhydrous P2S5 (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl5 (>99.9%), and anhydrous TaF5 (>99.9%) in a mortar at a molar ratio of 2.15:0.47:0.5:0.6:0.1:0.04:0.02 and pre-grind at room temperature for 30 min until a uniformly mixed powder is formed, ensuring that the raw material particles are initially in contact and fused.
[0055] S2. In an argon glove box, transfer the mixture obtained in S1 together with 60 g of zirconia balls with a diameter of 10 mm into a 50 mL zirconia ball mill jar, so that the mass ratio of zirconia balls to material (ball-to-material ratio) is 30:1. Use a fluororubber sealing ring to seal the ball mill jar to ensure that the inside of the jar is in a sealed state to prevent air from entering or material from leaking during subsequent ball milling.
[0056] S3. In an argon glove box, fix the sealed zirconia ball mill jar in a high-energy ball mill. Set the ball mill speed to 500 rpm / min and the total ball milling time to 15 h. The ball milling program adopts a cyclic mode, specifically: rotate clockwise for 10 min → rest for 5 min → rotate counterclockwise for 10 min → rest for 5 min. Repeat this cycle until the set ball milling time is reached to obtain amorphous precursor powder.
[0057] S4. Collect the obtained amorphous precursor powder in an argon glove box and press it into a sheet-like preform using a tablet press. Pack the sheet-like preform into a quartz ampoule and vacuum seal the ampoule using a vacuum sealing machine to ensure that the preform is completely isolated from the air.
[0058] S5. Place the sealed ampoule into a tube furnace, set the heating rate to 2℃ / min, heat to 500℃, and maintain this temperature for calcination for 5 hours. After calcination, close the tube furnace and allow the ampoule to cool naturally to room temperature. Open the ampoule, remove the calcined product, grind it into powder, and sieve it through a standard sieve to obtain the product with the chemical formula Li. 5.5 P 0.94 Ta 0.0 6S 4.5 F 0.1 Cl 0.7 Br 0.6 I 0.1 LPTSFCBI sulfide solid electrolyte.
[0059] Preparation Example 2 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous TaF₅ (>99.9%) are mixed in a molar ratio of 2.1:0.48:0.7:0.5:0.1:0.02:0.02; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.5 P 0.96 Ta 0.0 4S 4.5 F 0.1 Cl 0.8 Br 0.5 I 0.1 The LPTSCBI sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0060] Preparation Example 3 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous TaF₅ (>99.9%) are mixed in a molar ratio of 2.05:0.49:0.7:0.6:0.1:0:0.02; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.5 P 0.98 Ta 0.02 S 4. 5F 0.1 Cl 0.7 Br 0.6 I 0.1 The LPTSCBI sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0061] Preparation Example 4 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous TaF₅ (>99.9%) are mixed in a molar ratio of 2.2:0.46:0.6:0.4:0.1:0.06:0.02; in S5, a product with the chemical formula Li₂S₅ is obtained.5.5 P 0.92 Ta 0.0 8S 4.5 F 0.1 Cl 0.9 Br 0.4 I 0.1 The LPTSCBI sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0062] Preparation Example 5 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous TaF₅ (>99.9%) are mixed in a molar ratio of 2.15:0.47:0.45:0.6:0.15:0.03:0.03; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.5 P 0.94 Ta 0.06 S 4.5 F 0.15 Cl 0.6 Br 0.6 I 0.15 The LPTSCBI sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0063] Preparation Example 6 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous TaF₅ (>99.9%) are mixed in a molar ratio of 2.15:0.47:0.55:0.5:0.15:0.03:0.03; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.5 P 0.94 Ta 0.06 S 4.5 F 0.15 Cl 0.7 Br 0.5 I 0.15 The LPTSCBI sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0064] Preparation Example 7 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous TaF₅ (>99.9%) are mixed in a molar ratio of 2.15:0.47:0.45:0.55:0.2:0.04:0.02; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.5 P 0.94 Ta 0.06 S 4.5 F 0.1 Cl 0.75 Br 0.55 I 0.2 The LPTSCBI sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0065] Preparation Example 8 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous TaF₅ (>99.9%) are mixed in a molar ratio of 2.15:0.47:0.5:0.6:0.1:0.02:0.04; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.5 P 0.94 Ta 0.0 6S 4.5 F 0.2 Cl 0.6 Br 0.6 I 0.1 The LPTSCBI sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0066] Preparation Example 9 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), anhydrous LiI (>99.9%), anhydrous Li₃N (>99.9%), NbCl₅ (>99.9%), and anhydrous NbF₅ (>99.9%) are mixed in a molar ratio of 1.95:0.47:0.5:0.65:0.1:0.2:0.03:0.03; in S5, a electrolyte with the chemical formula Li₂S₅ is obtained. 5.75 P 0.94 Nb 0.06 S 4.3 N 0.2 F 0.15 Cl 0.65 Br 0.65 I 0.1 The LPNSNFCBI sulfide solid electrolyte. Everything else is the same as in Preparation Example 1; Preparation Example 10 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous Sb₂S₃ (>99.9%), anhydrous LiF (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), and anhydrous LiI (>99.9%) are mixed in a molar ratio of 1.96:0.47:0.03:0.09:0.15:0.65:0.65:0.1; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.65 P 0.9 4Sb 0.06 S 4.4 Se 0.09 F 0.15 Cl 0.65 Br 0.65 I 0.1 The LPSSSFCBI sulfide solid electrolyte. Everything else is the same as in Preparation Example 1; Preparation Example 11 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous GeS₂ (>99.9%), anhydrous MoS₂ (>99.9%), anhydrous SnS₂ (>99.9%), anhydrous SiS₂ (>99.9%), anhydrous Li₂Te (>99.9%), anhydrous LiF (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), and anhydrous LiI (>99.9%) are mixed in a molar ratio of 2:0.47:0.015:0.015:0.015:0.015:0.1:0.15:0.6:0.6:0.1; in S5, a product with the chemical formula Li₂ is obtained. 5.65 P 0.94 Ge 0.015 Mo 0.015 Sn 0.015 Si 0.015 S 4.47 Te 0.1 F 0.15 Cl 0.6 Br 0.6 I 0.1 The LPGMSSSTFCBI sulfide solid electrolyte was prepared in the same manner as in Example 1. Preparation Example 12 This preparation example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous Al₂S₃ (>99.9%), anhydrous In₂S₃ (>99.9%), Fe₂S₃ (>99.9%), anhydrous ZnS (>99.9%), anhydrous LiBH₄ (>99.9%), anhydrous LiF (>99.9%), anhydrous LiCl (>99.9%), anhydrous LiBr (>99.9%), and anhydrous LiI (>99.9%) are prepared in a ratio of 2.0675:0.47:0.0075:0.0075:0.0075:0.015: A mixture with a molar ratio of 0.1:0.15:0.65:0.65:0.1 was prepared in S5 to obtain a product with the chemical formula Li. 5.785 P 0.94 Al 0.015 In 0.015 Fe 0.015 Zn 0.015 S 4.5 (BH4) 0.1 F 0.15 Cl 0.65 Br 0.65 I0.1 The LPAIFZSBHFCBI sulfide solid electrolyte. Everything else is the same as in Preparation Example 1.
[0067] Compare with Example 1 This comparative example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, except that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), and anhydrous LiCl (>99.9%) are mixed in a molar ratio of 5:1:2; in S5, an LPSC sulfide solid electrolyte with the chemical formula Li₆PS₅Cl is obtained. Everything else is the same as in Preparation Example 1.
[0068] Compare with Example 2 This comparative example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), and anhydrous TaCl₅ (>99.9%) are mixed in a molar ratio of 2.65:0.47:0.7:0.06; in S5, a product with the chemical formula Li₆P₅ is obtained. 0.94 Ta 0.06 S5Cl LPTSC sulfide solid electrolyte. Other preparations are the same as in Example 1.
[0069] Compare with Example 3 This comparative example provides a doped sulfide solid electrolyte. The preparation process of this doped sulfide solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), and anhydrous LiBr (>99.9%) are mixed in a molar ratio of 2:0.5:0.75:0.75; in S5, a product with the chemical formula Li₂S₅ is obtained. 5.5 PS 4.5 Cl 0.75 Br 0.75 The LPSCB sulfide solid electrolyte. Everything else is the same as in Preparation Example 1.
[0070] Compare with Example 4 This comparative example provides a sulfide-doped solid electrolyte. The preparation process of this sulfide-doped solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous TaCl₅ (>99.9%), and anhydrous LiBr (>99.9%) were mixed in a molar ratio of 2.15:0.47:0.45:0.06:0.75; in S5, a electrolyte with the chemical formula Li₂S₅ is obtained. 5.5P 0.94 Ta 0.06 S 4.5 Cl 0.75 Br 0.75 The LPTSCB sulfide solid electrolyte was prepared in the same manner as in Example 1.
[0071] Compare with Example 5 This comparative example provides a sulfide-doped solid electrolyte. The preparation process of this sulfide-doped solid electrolyte is described in Preparation Example 1, with the difference being that in S1, the raw materials anhydrous Li₂S (>99.9%), anhydrous P₂S₅ (>99.9%), anhydrous LiCl (>99.9%), anhydrous TaCl₅ (>99.9%), anhydrous TaF₅ (>99.9%), and anhydrous LiBr (>99.9%) are mixed in a molar ratio of 2.15:0.47:0.5:0.04:0.02:0.7; in S5, a electrolyte with the chemical formula Li₂S₅ is obtained. 5.5 P 0.94 Ta 0.06 S 4.5 F 0.1 Cl 0.7 Br 0.7 The LPTSFCB sulfide solid electrolyte. Everything else is the same as in Preparation Example 1.
[0072] Example 1 This embodiment provides an all-solid-state battery. The preparation process of the all-solid-state battery is as follows: The LPTSCBI sulfide solid electrolyte provided in Preparation Example 1 is ground and mixed with NCM and VGCF at a mass ratio of 30:68.5:1.5, and then placed in a zirconia ball mill jar and ball-milled at 200 rpm for 4 h to prepare a composite cathode powder. 100 mg of the LPTSCBI sulfide solid electrolyte provided in Preparation Example 1 is added to a model battery, and the powder is cold-pressed at 400 MPa for 10 min using a tablet press; 10 mg of the composite cathode powder is added to one side of the model battery, and cold-pressed at 400 MPa for 10 min using a tablet press; 80 mg of lithium indium powder is added to the other side of the model battery, and cold-pressed at 400 MPa for 10 min using a tablet press, and the all-solid-state battery is assembled.
[0073] Example 2 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSCBI sulfide solid electrolyte provided in Preparation Example 2. Everything else is the same as in Example 1.
[0074] Example 3 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSCBI sulfide solid electrolyte provided in Preparation Example 3. Everything else is the same as in Example 1.
[0075] Example 4 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSCBI sulfide solid electrolyte provided in Preparation Example 4. Everything else is the same as in Example 1.
[0076] Example 5 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSCBI sulfide solid electrolyte provided in Preparation Example 5. Everything else is the same as in Example 1.
[0077] Example 6 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSCBI sulfide solid electrolyte provided in Preparation Example 6. Everything else is the same as in Example 1.
[0078] Example 7 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSCBI sulfide solid electrolyte provided in Preparation Example 7. Everything else is the same as in Example 1.
[0079] Example 8 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSCBI sulfide solid electrolyte provided in Preparation Example 8. Everything else is the same as in Example 1.
[0080] Example 9 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPNSNFCBI sulfide solid electrolyte provided in Preparation Example 9. Everything else is the same as in Example 1.
[0081] Example 10 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPSSSFCBI sulfide solid electrolyte provided in Preparation Example 10. Everything else is the same as in Example 1.
[0082] Example 11 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPGMSSSTFCBI sulfide solid electrolyte provided in Preparation Example 11. Everything else is the same as in Example 1.
[0083] Example 12 This embodiment provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPAIFZSBHFCBI sulfide solid electrolyte provided in Preparation Example 12. Everything else is the same as in Example 1.
[0084] Comparative Example 1 This comparative example provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPSC sulfide solid electrolyte provided in Comparative Example 1. Everything else is the same as in Example 1.
[0085] Comparative Example 2 This comparative example provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSC sulfide solid electrolyte provided in Comparative Example 2. Everything else is the same as in Example 1.
[0086] Comparative Example 3 This comparative example provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPSCB sulfide solid electrolyte provided in Comparative Example 3. Everything else is the same as in Example 1.
[0087] Comparative Example 4 This comparative example provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSB sulfide solid electrolyte provided in Comparative Example 4. Everything else is the same as in Example 1.
[0088] Comparative Example 5 This comparative example provides an all-solid-state battery. The preparation process of this all-solid-state battery is described in Example 1, except that the solid electrolyte used is the LPTSFCB sulfide solid electrolyte provided in Comparative Example 5. Everything else is the same as in Example 1.
[0089] Performance testing: 1. Conductivity Test: Weigh 100 mg of solid electrolyte powder using an electronic balance. Add the solid electrolyte powder to a mold with a diameter of 10 mm, assemble the battery mold, and apply a pressure of 550 MPa for 5 min. Finally, use an electrochemical workstation to test the battery impedance R of the mold. Disassemble and measure the thickness L of the electrolyte sheet, and calculate the ionic conductivity σ = L / RS. See [link to test results] for details. Figure 1 .from Figure 1 It can be seen that the doped sulfide solid electrolyte Li prepared in Example 1... 5.5 P 0.94 Ta 0.0 6S 4.5 F 0.1 Cl 0.7 Br 0.6 I 0.1 It exhibits excellent ion-conducting properties with a conductivity of 10.5 mS / cm at room temperature (25℃) and 2.2 mS / cm at low temperature (-20℃).
[0090] 2. SEM (Scanning Electron Microscopy) characterization: 2.1 The morphology of the doped sulfide solid electrolyte provided in Example 1 was characterized using SEM. The characterization results can be found in [reference needed]. Figure 2 .
[0091] 2.2 The morphology of the negative electrodes obtained after disassembly from the all-solid-state batteries provided in Example 1 and Comparative Example 1 after 10 cycles was characterized using SEM. The characterization results can be found in [link to SEM documentation]. Figure 4 .from Figure 4 Figure (a) and Figure 4 As can be seen from the comparison in Figure (b), compared to Comparative Example 1, the negative electrode of Example 1 has a relatively dense and uniform dynamic adaptive interface layer containing LiBr, LiI and LiF.
[0092] 3. TEM (Transmission Electron Microscopy) Characterization: The morphology of the positive electrodes obtained after disassembly from the all-solid-state batteries provided in Example 1 and Comparative Example 1 after 10 cycles was characterized using TEM. The characterization results are shown in [link to documentation]. Figure 3 .from Figure 3 Figure (a) and Figure 3 As can be seen from the comparison in Figure (b), compared to Comparative Example 1, the cathode of Example 1 has an antioxidant LiTaO3 / LiF gradient cathode composite interface layer formed on the cathode.
[0093] 4. Rate Performance Test: The rate performance of the all-solid-state batteries provided in Examples 1-12 and Comparative Examples 1-5 at -20℃ was tested at 0.1C to 2C. The test process was as follows: After the ambient temperature stabilized at -20±0.5℃, the following steps were performed sequentially: ① First, three complete charge-discharge cycles were performed at a current of 0.05C to activate the battery and stabilize its state; ② Using a constant current-constant voltage (CC-CV) method, the battery was charged at a constant current of 0.1C to the cutoff voltage of 3.68V, and then charged at a constant voltage until the current dropped to 0.05C to ensure that the battery was fully charged. After charging, the battery was left to stand in an open circuit at -20℃ for 30 minutes to allow the battery to reach an equilibrium state; then, the battery was discharged at a constant current of 0.1C to the discharge cutoff voltage of -0.61V. After discharging, the battery was left to stand for 30 minutes; ③ The battery was discharged incrementally from 0.2C to 2C. Charging: Before each discharge rate, repeat the CC-CV charging process in step ② to charge the battery to a full charge of 3.68V. After charging, allow it to rest for 30 minutes. Discharging: Perform constant current discharge sequentially at 0.33C, 0.5C, 1C, and 2C until the discharge cutoff voltage of -0.61V is reached for each. Resting: After each discharge, allow it to rest for 30 minutes before starting the next charging rate. See Table 1 for test results.
[0094] Table 1
[0095] 5. Cyclic Performance Test: The all-solid-state batteries provided in Examples 1-12 and Comparative Examples 1-5 were tested for their 0.33C cycle performance at -20℃. The test procedure was as follows: After the ambient temperature stabilized at -20±0.5℃, the following steps were performed sequentially: ① First, three complete charge-discharge cycles were performed at a current of 0.05C to activate the battery and stabilize its state; ② Using a constant current-constant voltage (CC-CV) method, the battery was charged at a constant current of 0.33C to the cutoff voltage of 3.68V, and then charged at a constant voltage until the current dropped to 0.05C to ensure that the battery was fully charged. After charging, the battery was left to stand in an open circuit at -20℃ for 30 minutes to allow the battery to reach an equilibrium state; then, the battery was discharged at a constant current of 0.33C to the discharge cutoff voltage of -0.61V. After discharging, the battery was left to stand for 30 minutes; ③ Step ② was repeated for 50 cycles. The test results are shown in Table 2.
[0096] Table 2
[0097] As can be seen from the test results in Tables 1 and 2, under low-temperature (-20℃) conditions, the electrochemical performance of Examples 1-12 is higher than that of Comparative Examples 1-5. This is because the sulfide solid electrolyte, through precise control of the cation and anion co-doping strategy, can not only effectively improve the interfacial stability between the positive and negative electrode active materials and the sulfide electrolyte under low-temperature conditions, but also, the interface optimization brought about by co-doping endows the electrode-electrolyte interface with good mechanical flexibility, which can effectively alleviate the stress damage caused by electrode volume shrinkage at low temperatures and significantly reduce the solid-solid contact loss at the active material / electrolyte interface.
[0098] Examples 1-8 involve using Ta with high ionic conductivity 5+ F - ,Br - I - Co-doping in LPSCs enables the solid-state battery to form an antioxidant LiTaO3 / LiF gradient positive electrode composite interface layer and a LiBr / LiI / LiF negative electrode dynamic adaptive interface layer during cycling. This improves the interfacial stability of the positive and negative electrode active materials and the sulfide electrolyte under low-temperature conditions, optimizes the solid-solid contact at the interface, and further significantly improves the rate performance and cycle stability of the battery while improving the low-temperature service performance of sulfide solid-state batteries.
[0099] The foregoing has provided a detailed description of a sulfide-doped solid electrolyte, its preparation method, electrode, and solid-state battery provided in the embodiments of this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.
Claims
1. A sulfide-doped solid electrolyte, characterized in that, The doped sulfide solid electrolyte is a sulfide solid electrolyte co-doped with cations and anions, wherein the cations include Ta 5+ 、Nb 5+ Sb 5+ 、Ge 4+ Mo 4+ Sn 4+ Si 4+ Al 3+ In 3+ Fe 2+ Fe 3+ and Zn 2+ At least one of the following, the anion including F - Cl - ,Br - I - Te 2- Se 2- N 3- and BH4 - At least three of them.
2. The doped sulfide solid electrolyte according to claim 1, characterized in that, The chemical formula of the doped sulfide solid electrolyte is: Li 5.5 P 1-x Ta x S 4.5 F a Cl 1.5-a-b-c Br b I c , of which 0 <x≤0.1,0<a≤1,0<b≤1,0<c≤1。 3. The doped sulfide solid electrolyte according to claim 2, characterized in that, 0.02≤x≤0.08, 0.1≤a≤0.2, 0.4≤b≤0.6, 0.1≤c≤0.
2.
4. The method for preparing a doped sulfide solid electrolyte according to any one of claims 1 to 3, characterized in that, include: A premix is provided, the premix comprising raw materials for a sulfide solid electrolyte and a dopant source; The premixed material is prepared into a doped sulfide solid electrolyte by ball milling, high-temperature quenching, or liquid phase method.
5. The method for preparing a doped sulfide solid electrolyte according to claim 4, characterized in that, The chemical formula of the doped sulfide solid electrolyte is: Li 5.5 P 1-x Ta x S 4.5 F a Cl 1.5-a-b-c Br b I c , of which 0 <x≤0.1,0<a≤1,0<b≤1,0<c≤1; The preparation method of the doped sulfide solid electrolyte includes: Li2S, P2S5, LiCl, LiBr, LiI, TaCl5 and TaF5 were mixed according to the molar ratio of (2+2.5x) : (1-x) / 2 : (1.5-bc-5x) : b : c : (xa / 5) : a / 5 to obtain a premix. The premix was ball-milled to obtain an amorphous precursor; The amorphous precursor was calcined to obtain a sulfide-doped solid electrolyte.
6. The method for preparing a doped sulfide solid electrolyte according to claim 5, characterized in that, The ball milling time for the ball milling process is 5 hours to 75 hours; and / or, The ball milling process is performed at a speed of 200 rpm to 1300 rpm; and / or, The ball-to-material ratio for the ball milling process is (1~50):
1.
7. The method for preparing a doped sulfide solid electrolyte according to claim 5, characterized in that, The calcination temperature for the calcination treatment is 200℃~600℃; and / or, The calcination time for the calcination treatment is 2 hours to 7 hours; and / or, The calcination process is constant temperature calcination.
8. An electrode sheet, characterized in that, The electrode active material is mixed with the doped sulfide solid electrolyte prepared by the method described in any one of claims 1 to 3 or the method described in any one of claims 4 to 7.
9. The electrode sheet according to claim 8, characterized in that, The electrode further includes a conductive agent, and the mass ratio of the electrode active material, the doped sulfide solid electrolyte, and the conductive agent is (5~35):(64.5~90):(0.5~5); and / or, The electrode active material is a positive electrode active material, which includes at least one of NCM, LiFePO4, LiCoO2 and LRMOs.
10. A solid-state battery, characterized in that, Including the electrode as described in claim 8 or 9.